2005
DOI: 10.1128/aem.71.11.7523-7527.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Localization, and Phylogeny of Abundant Populations of Crenarchaeota in Anaerobic Granular Sludge

Abstract: Eight anaerobic granular sludges were surveyed for Crenarchaeota using rRNA gene cloning. Microbial arrangement and substrate uptake patterns were elucidated by fluorescent in situ hybridization and beta imaging. Group 1.3 Crenarchaeota represented up to 50% of Archaea and 25% of the total microbiota in five sludges. Crenarchaeota were localized in close association with methanogenic Archaea.Crenarchaeal phylogeny has been fundamentally changed by the isolation of novel small-subunit rRNA gene clones from meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…Approximately 51% and 21% of the clones analyzed for reactors 1 and 2, respectively, were closely related to uncultured archaeal 16S rRNA gene clones that were not targeted by our probe set (Figure 3). In addition to these uncultured methanogen-like groups, it is known that clones assigned to the candidate taxon WSA2 of the Euryarchaeota and the subphylum C2 of the Crenarchaeota have been retrieved from some methanogenic sludges in abundance (Chouari et al, 2005;Collins et al, 2005), although the archaeal rRNA gene cloning analysis for the sludges in this study showed no detection of such phylotypes. Thus there is a further need to develop additional scissor probes to cover these uncultured Archaea to better determine the abundance of the archaeal populations in natural and engineered environments in the future.…”
Section: Discussionmentioning
confidence: 46%
“…Approximately 51% and 21% of the clones analyzed for reactors 1 and 2, respectively, were closely related to uncultured archaeal 16S rRNA gene clones that were not targeted by our probe set (Figure 3). In addition to these uncultured methanogen-like groups, it is known that clones assigned to the candidate taxon WSA2 of the Euryarchaeota and the subphylum C2 of the Crenarchaeota have been retrieved from some methanogenic sludges in abundance (Chouari et al, 2005;Collins et al, 2005), although the archaeal rRNA gene cloning analysis for the sludges in this study showed no detection of such phylotypes. Thus there is a further need to develop additional scissor probes to cover these uncultured Archaea to better determine the abundance of the archaeal populations in natural and engineered environments in the future.…”
Section: Discussionmentioning
confidence: 46%
“…MCG are present in terrestrial hot springs , deep oceanic subsurface sediments (Parkes et al, 2005), deep terrestrial subsurface (Inagaki et al, 2003), continental shelf sediments (Vetriani et al, 1998), ancient marine sapropels (Coolen et al, 2002), petroleum-contaminated soil (Kasai et al, 2005), termite guts (Friedrich et al, 2001), mud volcanoes (Heijs et al, 2007), methane hydrate-containing marine sediments (Inagaki et al, 2006), landfill leachate (Huang et al, 2003), anaerobic wastewater reactors (Collins et al, 2005), sulfidic springs (Elshahed et al, 2003), brackish lakes (Hershberger et al, 1996) and coastal salt marshes (Castro et al, 2004). Only 28 out of 4720 MCG sequences were retrieved from potentially oxic habitats (for example, database releases EU370096 and FJ560325).…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, the 16S rRNA gene clones retrieved from UASB sludges indicated the major microbial constituents to be those of the phyla Proteobacteria, Chloroflexi, Firmicutes, Spirochaetes, and Bacteroidetes in the domain Bacteria, and those of the classes Methanomicrobia, Methanobacteria, and Thermoplasmata in the domain Archaea (47). In addition, such studies have also shown that a large number of the clones assigned to candidate phyla (known as 'clone clusters') were frequently found in such ecosystems (7,8,10,20,31,48,55). However, there are still obstacles to precisely determining and monitoring the entire microbial community of sludge because of the limited number of datasets reported so far.…”
mentioning
confidence: 99%
“…So far, molecular-based community analyses have been performed for UASB granular sludges treating wastewater from a paper factory (41), a terephthalatemanufacturing plant (53), a beer brewery (13), and sucrose/ propionate/acetate-based artificial wastewater (44). In addition, the molecular characterization of UASB granules targeting specific microbial groups has also been reported (10,20,31). According to these studies, the 16S rRNA gene clones retrieved from UASB sludges indicated the major microbial constituents to be those of the phyla Proteobacteria, Chloroflexi, Firmicutes, Spirochaetes, and Bacteroidetes in the domain Bacteria, and those of the classes Methanomicrobia, Methanobacteria, and Thermoplasmata in the domain Archaea (47).…”
mentioning
confidence: 99%